2021
DOI: 10.1108/ilt-02-2021-0047
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of piston skirt coatings on the tribological performance of heavy-duty diesel engine under low viscosity lubricant

Abstract: Purpose The purpose of this paper was to improve the frictional wear resistance properties of piston skirts caused by the low viscosity lubricant by studying the tribological performance of three novel coating materials. Design/methodology/approach Comparative tribological examinations were performed in a tribological tester using the ring-block arrangement under two viscosity lubricants, the loading force was applied as 100 N, the speed was set to 60 r/min and the testing time was 180 min. Findings Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meng et al [216] and Yin et al [217] found the presence of the liquid lubricants significantly reduces the friction coefficient and the wear rate of the pure coating. Wang et al [218] prepared ultralow friction polymer composites by adding oil-loaded microcapsules into epoxy (EP) resin.…”
Section: Self-lubricating Materialsmentioning
confidence: 99%
“…Meng et al [216] and Yin et al [217] found the presence of the liquid lubricants significantly reduces the friction coefficient and the wear rate of the pure coating. Wang et al [218] prepared ultralow friction polymer composites by adding oil-loaded microcapsules into epoxy (EP) resin.…”
Section: Self-lubricating Materialsmentioning
confidence: 99%
“…11 The wear rate of the engine parts is influenced by the viscosity of the lubricant. Lowviscosity lubricants can result in an increase in the friction coefficient and wear, 12,13 while the utilization of certain additives or nanoparticles can lead to a reduction in frictional force and wear rate. 14 The investigation aims to explore alternative fuels derived from bioresources, specifically by blending palm oil with aluminum oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%